Healthcare resource utilization and associated cost analysis of the PROCLAIM study in patients with stage III non-small-cell lung cancer. (3rd October 2019) - Govindan, Ramaswamy; Senan, Suresh; Dickgreber, Nicolas; Provencio, Mariano; Wu, Yi-Long; Syrigos, Konstantinos; Parente, Barbara; Wilson, Michele; Ziemiecki, Ryan; Chouaki, Nadia; Hossain, Anwar; San Antonio, Belén; et al.
Abstract: Objective: To analyze patient-reported swallowing difficulties, healthcare resource utilization and associated costs during the PROCLAIM study. Methods: Patients with stage III non-squamous non-small cell lung cancer received pemetrexed-cisplatin (PemCis) combined with concurrent thoracic radiotherapy followed by consolidation pemetrexed, or concurrent chemoradiotherapy with etoposide-cisplatin (EtoCis) followed by standard consolidation chemotherapy. Patient - reported swallowing function was measured using diaries. Resource utilization (hospitalizations, transfusions, concomitant medications) was compared between treatment arms using Fisher's exact test and independent t -test. Medical resource use costs were analyzed using nonparametric Wilcoxon rank sum test. Results: Patient-reported difficulty in swallowing function (diary score ≥4) was 33.8% in the PemCis arm and 29% in the EtoCis arm. Overall resource use, including hospitalizations, was similar between treatment arms; however, fewer patients in the PemCis arm received transfusions and selected concomitant medications. Concurrent phase analyses were consistent with the overall study. A significantly lower percentage of patients (31.1% vs. 40.8%) were hospitalized in the PemCis arm. Total costs were significantly higher in the PemCis arm. Other medical costs (excluding study treatment costs) during the concurrent phase were lower for patients in the PemCis arm, due to significantly lower hospitalization costs and lower use of concomitant medications. Subgroup analysis yielded similar results. Conclusions: Patient-reported difficulty in swallowing post-baseline and resource utilization were consistent with previously reported safety outcomes. In the overall study, higher total costs for PemCis were driven by study drug cost. When adjusting for treatment duration, other monthly medical costs were favorable to PemCis. Patients on pemetrexed remained longer on therapy, suggesting better tolerability. Trial registration: ClinicalTrials.gov identifier: NCT00686959.